1992
DOI: 10.1002/hep.1840150414
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procollagen Peptides and Collagen Type Vi for the Assessment of Activity and Degree of Hepatic Fibrosis in Schistosomiasis and Alcoholic Liver Disease

Abstract: Schistosomiasis, in contrast to alcoholic liver disease, leads to presinusoidal hepatic fibrosis, which determines the prognosis of the disease. Because conventional liver function tests and liver biopsy specimens provide little information about the dynamics of the fibrotic process, we measured the serum concentrations of procollagen type III N-propeptide and procollagen type I C-propeptide, believed to mainly reflect collagen synthesis, and procollagen type IV C-propeptide and collagen type VI, two presumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…Comparing serum C-IV levels between groups, according to the clinical classification of patients with mansonic and hematobic schistosomiasis, Shahin et al (1992) found high serum levels in patients with hepatosplenic schistosomiasis. In Tanzania, a correlation between serum C-IV and clinical and sonographic signs of hepatosplenic schistosomiasis was observed, but it did not have enough sensitivity to be useful as a screening tool for fibrosis (Kardorff et al 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Comparing serum C-IV levels between groups, according to the clinical classification of patients with mansonic and hematobic schistosomiasis, Shahin et al (1992) found high serum levels in patients with hepatosplenic schistosomiasis. In Tanzania, a correlation between serum C-IV and clinical and sonographic signs of hepatosplenic schistosomiasis was observed, but it did not have enough sensitivity to be useful as a screening tool for fibrosis (Kardorff et al 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, SHAHIN et al (22) suggested that in contrast to alcoholic disease type IV, procollagen was only increased in the late stages of schistosomiasis, thus being a good marker for advanced stages of fibrosis. In this same study the patients were classified into three different forms: a simple clinical form without hepatic involvement compensated hepatosplenic and decompensated hepatosplenic.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic hepatitis, cirrhosis and hepatic schistosomiasis, C-VI serum levels were elevated, irrespective of the disease aetiology [20,23]. In all these liver diseases, a histologically proven progress of fibrosis was correlated with an increase in serum PIIINP levels and a relative decrease of serum C-VI levels [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…C-VI was quantified by a newly developed two-armed enzyme-linked immunosorbent assay (ELISA) system [22,23] based on competition of serial dilutions of the standard or the sample with a predetermined amount of rabbit antibodies to human placental C-VI. Uncompeted antibodies were then bound to C-VI immobilized on a 96-well microtitre plate and quantified using biotinylated goat anti-rabbit immunoglobulin G (IgG), followed by rabbit peroxidase antiperoxidase and extravidinperoxidase.…”
Section: Measurement Of Collagen Type-vi-related Antigensmentioning
confidence: 99%